The truth about grandparents - Ellis, Elina (2019)
A child relates strange things that might be heard about grandparents, but concludes that they are amazing
"Originally published as The Truth About Old People in 2019 by Pan Macmillan in the United Kingdom"--Page facing title page
Keywords: Grandparents -- Juvenile fiction; Old age -- Juvenile fiction; Picture books for children; Picture books for children; Picture books